Lactobacillus johnsonii and host communication: insight into modulatory mechanisms during health and disease - Arzola-Martínez, Llilian; Ravi, Keerthikka; Huffnagle, Gary B.; Lukacs, Nicholas W.; Fonseca, Wendy (Frontiers in Microbiomes, 2024)
Lactobacillus johnsonii is a commensal bacterium that has been isolated from vaginal and gastrointestinal (GI) tracts of vertebrate hosts, including humans, rodents, swine, and poultry.Lactobacillus-based probiotic supplements are popular because of the health advantages they offer. Species such as L. johnsonii are particularly interesting due to their potential healthpromoting properties. Here, we reviewed the research on specific strains of L. johnsonii that have been studied in the context of health and disease and delved into the underlying mechanisms that aid in preserving host homeostasis. The utilization of L. johnsonii strains has been widely linked to numerous health benefits in the host. These include pathogen antagonism, control of mucosal and systemic immune responses, reduction of chronic inflammation, modulation of metabolic disorders, and enhanced epithelial barrier. These findings suggest that L. johnsonii plays a critical role in maintaining host homeostasis, highlighting its potential as a probiotic.